Effects of handedness on brain oscillatory activity during imagery and execution of upper limb movements - Lajtos, Melissa; Barradas-Chacón, Luis Alberto; Wriessnegger, Selina Christin (Frontiers in Psychology, 2023)
Brain activation during left- and right-hand motor imagery is a popular feature used for brain–computer interfaces. However, most studies so far have only considered right-handed participants in their experiments. This study aimed to investigate how handedness influences brain activation during the processes of imagining and executing simple hand movements. EEG signals were recorded using 32 channels while participants repeatedly squeezed or imagined squeezing a ball using their left, right, or both hands. The data of 14 left-handed and 14 right-handed persons were analyzed with a focus on event-related desynchronization/synchronization patterns (ERD/S). Both handedness groups showed activation over sensorimotor areas; however, the right-handed group tended to display more bilateral patterns than the left-handed group, which is in contrast to earlier research results. Furthermore, a stronger activation during motor imagery than during motor execution could be found in both groups.